Online training report on: Agronomic Data Collection and Management Tools for Better Agricultural Research - Atassi, Layal; Attaher, Samar; Devkota Wasti, Mina Kumari; Nangia, Vinay (2024)
Excellence in Agronomy (EiA) and Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) are “One CGIAR” Initiatives that aim for sustainable intensification and climate change adaptation in addition to building resilient agrifood systems in the region to support smallholder farmers by providing evidence-based data-driven agronomy solutions. Thus, it is critical to improve agronomic research techniques and contexts by utilizing digital tools that enable researchers to develop and share FAIR digital data sets (findable, accessible, interoperable, and reusable). When data is shared under the same community-agreed-upon standards, making data interoperable allows the data to be reused for scientific research as inputs for different analyses and models to deliver insights and management options for stakeholders, including the ultimate beneficiaries, who are often poor farmers.